If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7z + 7 + 3z + -8 = 90 Reorder the terms: 7 + -8 + 7z + 3z = 90 Combine like terms: 7 + -8 = -1 -1 + 7z + 3z = 90 Combine like terms: 7z + 3z = 10z -1 + 10z = 90 Solving -1 + 10z = 90 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 10z = 90 + 1 Combine like terms: -1 + 1 = 0 0 + 10z = 90 + 1 10z = 90 + 1 Combine like terms: 90 + 1 = 91 10z = 91 Divide each side by '10'. z = 9.1 Simplifying z = 9.1
| -3(5x-4)=-18 | | 37+8k=k-(-4-7k) | | 7(4-x)=7x+2 | | -8x+2x+-16=-5x+7x | | 20x=9x+6 | | r+1+2r-15=37 | | 38=-6x-7x-27 | | 7p+5=11+6p | | 2x+99=5x+6 | | 8x+4x-68=34-5x | | X-2=15x+-9x | | 2x^2+5x+3=2x^2+8x | | -2=x/3-8 | | 4x-31=2x-9 | | 4x-31=2x-8 | | 10y^2+47y+9=0 | | 8x-2=(-9+7x) | | (15m-9)=(2m+19) | | 167=6+7(2+-7r) | | 5=x-3/2 | | 6x^2=5x+50 | | 42=6(k-5) | | 1+a+2=7 | | 3(x-5)=-3x-3 | | -.7x=1.4 | | 3x-9=4(x+3) | | 8+3x=10+3x | | -138=-36b+42 | | 5+16x=18x-5 | | .5x+3.1=.9x-0.1 | | (-6m^2+7n^2-4n)-[(7m^2-4m+7n)+(-7m^2)+4n^2]=0 | | .05x+3.1=.9x-.01 |